Insiders' profits, costs of trading, and market efficiency - Seyhun, H.Nejat (Journal of Financial Economics, 1986)
This study investigates the anomalous findings of the previous insider trading studies that any investor can earn abnormal profits by reading the Official Summary. Availability of abnormal profits to insiders, availability of abnormal profits to outsiders who imitate insiders, determinants of insiders' predictive ability, and effect of insider trading on costs of trading for other investors are examined by using approximately 60,000 insider sale and purchase transactions from 1975 to 1981. Implications for market efficiency and evaluation of abnormal profits to active trading strategies are discussed.